Evaluation of Serum Ferritin in Hospitalized Patients with COVID-19 as A Potential Biomarker for Assessing COVID-19 Severity (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Corona virus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), has become global pandemic. Proinûammatory mediator, serum ferritin is reported to be elevated significantly by different studies in COVID-19. Our study was aimed to find whether serum ferritin level can be employed as a biomarker to assess the disease severity in COVID-19 cases. Methods: This cross sectional observational study was carried out at Armed Forces Institute of Pathology (AFIP), a tertiary referral laboratory between 15 March 2020 and 15 June 2020. Total 2418 hospitalized RT-PCR confirmed COVID- 19 patients from Combined Military Hospital (CMH) were included in our study. Serum ferritin was measured by electrochemiluminescence immunoassay and was compared between the severe and non-severe groups. P-value < 0.05 was considered statistically significant. Results: Total patients were 2418, among them 337 (13.9%) from intensive care unit (ICU) and 2081 (86.1%) from non- ICU. Median age and IQR were 60.5 (51.5–68.0) years in ICU patients versus 38.0 (28-46.1) years in non-ICU patients (p